THE MAIN CHARACTER’S EGO DEFENSE MECHANISM AGAINST THE STORYLINE OF THE NOVEL CARITA CALIN BY APRILIA FATMAWATI - Bija Bijakni Al Janatan (Lingeduca: Journal of Language and Education Studies, 2026)
This study aims to examine the forms of ego defense mechanisms of the main character and their role in the development of the storyline in the novel Carita Calin by Aprilia Fatmawati. This study is motivated by the importance of understanding literary works not only as a representation of social reality, but also as a reflection of the psychological dynamics of the main character. The approach used is literary psychology based on Sigmund Freud's psychoanalytic theory, especially the concepts of id, ego, superego, and ego defense mechanisms. This research also emphasizes the novelty in the analysis of the relationship between the main character's ego defense mechanism and the development of the storyline in the novel. The method used is descriptive qualitative research with literature study techniques. The research data is in the form of quotes in the novel that show the symptoms of the main character's ego defense mechanism. Data collection techniques are carried out through the reading and recording methods, while data analysis is carried out through the identification, classification, and interpretation stages based on Freud's psychoanalytic theory. Next, the data is analyzed to see how it relates to the development of the storyline. The results of the study show that the main character, Caliandra Rowana (Calin), uses various ego defense mechanisms, such as repression, diversion, projection, rationalization, regression, formation reaction, denial, sublimation and fantasy. The dominant mechanisms are repression, diversion and projection, which show a tendency to use less adaptive defense strategies. These mechanisms not only reflect the psychological state of the main character, but also play a role in emerging, directing, and prolonging conflicts in the storyline. The main character's ego defense mechanism is closely related to the development of the storyline in the novel Carita Calin by Aprilia Fatmawati.